Multimodal Imaging of Disease-Associated Pigmentary Changes in Retinitis Pigmentosa - Schuerch, Kaspar (Retina, 2016)
PURPOSE: Using multiple imaging modalities we evaluated the changes in photoreceptor cells and RPE that are associated with bone spicule-shaped melanin pigmentation in retinitis pigmentosa (RP). METHODS: In a cohort of 60 RP patients, short-wavelength autofluorescence (SW-AF), near-infrared (NIR)-AF, NIR-reflectance (NIR-R), spectral domain optical coherence tomography (SD-OCT) and color fundus images were studied. RESULTS: Central AF rings were visible in both SW-AF and NIR-AF images. Bone spicule pigmentation was non-reflective in NIR-R, hypoautofluorescent with SW-AF and NIR-AF imaging and presented as intraretinal hyperreflective foci in SD-OCT images. In areas beyond the AF ring outer border, the photoreceptor ellipsoid zone (EZ) band was absent in SD-OCT scans and the visibility of choroidal vessels in SW-AF, NIR-AF and NIR-R images was indicative of reduced RPE pigmentation. Choroidal visibility was most pronounced in the zone approaching peripheral areas of bone spicule pigmentation; here RPE/Bruch’s membrane thinning became apparent in SD-OCT scans. CONCLUSIONS: These findings are consistent with a process by which RPE cells vacate their monolayer and migrate into inner retina in response to photoreceptor cell degeneration. The remaining RPE spread, undergo thinning and consequently become less pigmented. An explanation for the absence of NIR-AF melanin signal in relation to bone spicule pigmentation is not forthcoming.